Risk Factors Associated With Pediatric Asthma Hospitalization: A Retrospective Case-Control Study - Lucy Grace de los Angeles Luna Muñoz; Silvia Ursula Revoredo Llanos; Karina Ordaya-Gonzales; Liliana Arriola-Montenegro; Andres Chaponan-Lavalle; Jose Arriola-Montenegro (Journal of Family and Reproductive Health)
Objective: To evaluate the risk factors associated with asthma in children hospitalized at Hospital Belen de Trujillo. Materials and methods: An analytical study of retrospective cases and controls was carried out in which 258 clinical histories of children between 5 to 14 years of age who were hospitalized in the Hospital Belen de Trujillo (HBT) during the period 2015-2019 were included, which were grouped into 129 histories of children who had been hospitalized for asthma (cases) and 129 histories of children hospitalized for a different cause (controls). The frequency distribution will be calculated, the Chi-square statistical test will be used, the odds ratio will be obtained and the 95% confidence interval will be calculated; finally, a multivariate analysis will be performed by means of logistic regression to determine whether the influence of other variables generates a greater risk of developing asthma in children. Results: The multivariate analysis showed that the factors: cesarean delivery, non-exclusive breastfeeding, history of bronchiolitis, obesity and maternal age together predict 92. 0% of the cases of asthma; however, taking the influence of all the factors at the same time, it was found that the cesarean delivery route, non-exclusive breastfeeding, obesity and maternal age are significant for the regression (p<0.05), while the factor history of bronchiolitis is not significant (p>0.05). Likewise, when the bivariate analysis of the five variables studied was performed and the Chi-square test was applied, it was found that all five factors were significant (p<0.05) for asthma in children at Hospital Belen de Trujillo. Conclusion: The factors cesarean delivery route, non-exclusive breastfeeding, history of bronchiolitis, obesity and maternal age are associated with asthma in children hospitalized at HBT.